PREVENTION OF EARLY MARRIAGE THROUGH A TALK SHOW ON HEALTHY FOOD CONSUMPTION BASED ON ANCIENT AGRICULTURE - Dewiantika Azizah; Lucky Dewanti; Suriyani Suriyani; Dadan Samsul (Jurnal Abdisci, 2025)
Abstract. Early marriage is one of the social phenomena where marriage occurs due to unwanted pregnancy, due to promiscuous sexual behavior. The impact of early marriage is that adolescents who experience drowning syndrome during pregnancy so that their children have low birth weight (BBLR) and also miscarriages. The purpose of this community service is to provide counseling in the form of a talk show about the prevention of early marriage through the consumption of healthy food based on ancient agriculture and to find out the response of residents to the talk show activities carried out. The method used by the author in this study is using the following methods: (a) a survey of residents who have been married early, (b) sharing and discussing talk show materials with ancient agricultural experts and (c) interviews with residents regarding the response in these activities. The results of this counseling activity provide education that is quite effective to increase the knowledge of adolescents, regarding the prevention of early marriage which is carried out by consuming healthy food by participating in ancient agricultural activities. The social impact of residents gives a positive response to the talk show activities, the environmental impact felt is the enthusiasm of residents to participate in the implementation of ancient agriculture, and the economic impact is that through the ancient agriculture program, residents are not only equipped with knowledge but can create businesses by producing several products with economic value.